Ofensividade, crimes de perigo abstrato e uso de drogas - Coelho, Gustavo Tozzi (2016)
This present work aims to show the importance of the principle of offensiveness in criminal law and its relationship with the complex situation of the use of drugs on the current brazilian legislation. Thus, the initial step will be given from the historical context that involves the notion of offensiveness, as well as the assumption of the principle of offensiveness in criminal matters: no crime without offense to legal-criminal interest (nullum crimen sine iniuria). Considering that the principle of offensiveness operates in two different planes (first, while the criminal legislator guidance about which conducts are worthy of criminal supervision; second, while hermeneutical canon to magistrate's aid in the interpretation of the case), will be studied if – effectively – the offence to a legal interest it is or not a legal constitutional enforcement. On the basis of the analysis as the model of crime as offense to legal interest, will be made some considerations about such understanding, as well as pointed to the conceptions about the Legal Interest Theory. Once addressed such concepts that include the modalities of offense in criminal law (damage/violation; concrete put-in-danger; care-ofdanger) according to the reading which makes the typical tort as a perversion of the relationship onto-anthropological care-of-danger, it will be possible to move forward in the discussion on the problems that abstract danger crimes involves and their deficits denied. Hence, next on the controversy inherent in the situation of the use of drugs and their legal implications, differentiating the circumstances which exist between the user and the chemical dependent. To do so, it will be draw a parallel with the notion of autonomy and the principle of respect for autonomy when it comes to user and the dependent. In the end, will be studied the issue of paternalism (criminal law) and their chances of justification. The methodology used for the desired purpose of this work takes place through interdisciplinary literature review on the topic, leaving criminal and legal references and other related materials in the context of Criminal Sciences.